Beliefs regarding the use of imaging among patients with low back pain: A cross-sectional study in the context of a middle-income country - Diniz, Leandro M.; Lemes, Ítalo R. [UNESP]; Freire, Ana P. C. F.; Guimarães, Ana F.; Ferreira, Lucas A. C.; Franco, Marcia R.; Verhagen, Arianne P.; Simoneau, Guy; Pinto, Rafael Z. (Wiley, 2025)
Introduction: Patients with low back pain may play an active role in the prescription of excessive spine imaging. Objective: To determine the proportion of patients with low back pain who have beliefs not aligned with current evidence regarding the use of imaging and to identify factors associated with these beliefs. Design: Secondary analysis of baseline data of a previously published randomized clinical trial. Setting: Outpatient physical therapy clinic in a middle-income country. Patients: Individuals with non-specific low back pain. Methods: Outcome variables were two statements assessing the extent of patient agreement on the need for imaging in the management of low back pain. The predictor variables were age, educational level, duration of symptoms, disability level, pain intensity in the last 24 hours, beliefs about inevitable consequences of low back pain (assessed using the Back Belief Questionnaire), and having received imaging previously. Multivariable logistic models were used for data analysis. Main Outcome Measure(s): Level of agreement with Statement 1: X-rays or scans are necessary to get the best medical care for low back pain and Statement 2: Everyone with low back pain should have spine imaging. Results: A total of 159 patients were included. Of these, 88.1% believed that imaging was necessary for the best medical care for low back pain and 62.9% believed that everyone with low back pain should obtain imaging. Lower scores on the Back Belief Questionnaire were associated with beliefs that imaging was necessary (odds ratio [OR] = 0.90, 95% confidence interval [CI]: 0.81, 0.99) and low education level was associated with the belief that everyone with low back pain should obtain imaging (OR = 3.03, 95% CI: 1.38, 6.61), after controlling for potential confounders. Conclusion: Nearly 90% of patients believe that spine imaging is necessary for the management of low back pain. Beliefs about the inevitable consequences of low back pain and low education level may be factors that need to be considered when developing new interventions.